Harmonisasi Keluarga: Telaah Fenomena Commuter Marriage di Indonesia - Uyun, Qurratul; Rohmatulloh, Muhammad Sabiq (Tasamuh: Jurnal Studi Islam, 2022)
This paper examines efforts to maintain harmony for commuter marriage families. The basic thing to do to form a sakinah family for commuter marriage actors is to carry out the rights and obligations of each family member. Because the concept of a sakinah family will not be realized if it only relies on one person, it is required to create cooperation between family members with one. The research method uses a qualitative with an empirical approach. The results show that to maintain the harmony of the commuter marriage family, it is necessary to fulfil several aspects such as financial aspects, biological aspects, and psychological aspects, but to fulfil these aspects, additional steps are needed to create a harmonious family. These steps are needed to create a harmonious family. These steps are obtained using Bourdieu’s theory, namely social capital, charismatic, and habitus.